2019
DOI: 10.1111/tra.12655
|View full text |Cite
|
Sign up to set email alerts
|

Structure of membrane tethers and their role in fusion

Abstract: Vesicular transport between different membrane compartments is a key process in cell biology required for the exchange of material and information. The complex machinery that executes the formation and delivery of transport vesicles has been intensively studied and yielded a comprehensive view of the molecular principles that underlie the budding and fusion process. Tethering also represents an essential step in each trafficking pathway. It is mediated by Rab GTPases in concert with so-called tethering factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 122 publications
(193 reference statements)
1
61
0
Order By: Relevance
“…An important aspect of membrane geometry in cells is the speed of the curvature delivery/extraction during fusion of membrane organelles, and the speed of alterations in their volume and surface area. For instance, the pulling tether is stable when it is formed slowly, and can be disrupted at higher speed [ 26 , 27 , 28 , 29 ]. Experiments with quick freezing of synapses, after their stimulation, demonstrated that lipid physics is responsible for these extremely fast formations of buds, on the presynaptic membrane after the fusion of synaptic vesicles with it [ 30 , 31 ].…”
Section: Factors Determining the Membrane Curvaturementioning
confidence: 99%
“…An important aspect of membrane geometry in cells is the speed of the curvature delivery/extraction during fusion of membrane organelles, and the speed of alterations in their volume and surface area. For instance, the pulling tether is stable when it is formed slowly, and can be disrupted at higher speed [ 26 , 27 , 28 , 29 ]. Experiments with quick freezing of synapses, after their stimulation, demonstrated that lipid physics is responsible for these extremely fast formations of buds, on the presynaptic membrane after the fusion of synaptic vesicles with it [ 30 , 31 ].…”
Section: Factors Determining the Membrane Curvaturementioning
confidence: 99%
“…In vivo, SNAREs collaborate with other factors including Sec1/Munc18 (SM) proteins and multisubunit tethering complexes (MTCs). SM proteins function as SNARE chaperones, regulating the assembly of SNARE complexes (11,(15)(16)(17), whereas MTCs act upstream of SNARE complex assembly, mediating the initial attachment of a vesicle to its target membrane (17)(18)(19). Vesicle tethering canonically involves interactions between MTCs and membrane-associated Rab proteins, but can also involve MTC•SNARE, MTC•coat, MTC•golgin, and/or MTC•phospholipid interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The largest family of MTCs is the CATCHR (Complexes Associated with Tethering Containing Helical Rods) family, whose members function largely in trafficking to and from the Golgi (19,26,27). The CATCHR-family complexes -GARP/EARP, exocyst, conserved oligomeric Golgi (COG), and Dsl1 -contain 3-8 subunits each.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, SNAREs collaborate with other factors including Sec1/Munc18 (SM) proteins and multisubunit-tethering complexes (MTCs). SM proteins function as SNARE chaperones, regulating the assembly of SNARE complexes (11,(15)(16)(17), whereas MTCs act upstream of SNARE complex assembly, mediating the initial attachment of a vesicle to its target membrane (17)(18)(19). Vesicle tethering canonically involves interactions between MTCs and membrane-associated Rab proteins but can also involve MTCSNARE, MTCcoat, MTCgolgin, and/or MTCphospholipid interactions.…”
mentioning
confidence: 99%